Determinants of vaccination uptake among pregnant women in Kumasi: A multi-centre cross-sectional study - Collins Atta Poku; Grace Agyeiwaa Owusu; Priscilla Gyamfuah; Gertrude Addae; Catherine Kroamah Dwumfour; Doris Hagan; Cynthia Yaba Kumah; Daisy Afra Lumor; Veronica Dzomeku (PLoS ONE, 2025)
Introduction Pregnant women are a high-risk group for severe symptoms and complications during pandemics, and vaccination is an important measure to prevent infection and protect both the mother and the foetus. However, there has been limited research on vaccination uptake by pregnant women in Ghana, especially during pandemics. Aim This study investigated the determinants of vaccination uptake among pregnant women in Kumasi, Ghana. Methods A multi-centre cross-sectional study assessed factors influencing vaccination uptake among pregnant women in Ghana. Using a multi-stage sampling technique, the respondents were selected from three (3) hospitals in Kumasi. Data was analysed through descriptive, ANOVA, correlation and linear regression at a significance level of 0.05. Results On perception of vaccination during pregnancy, 184 (71.9%) indicated their readiness to accept vaccination when requested. The higher the academic qualification of respondents, the more likely they are to receive vaccination. While the significant factor influencing vaccination uptake was “Complacency”, which explained 31.5% of the variance of the vaccination uptake decision-making, key barriers to vaccination uptake included doubts about the vaccine, fear of side effects, fear of injection and the belief that vaccination is a conspiracy. Conclusion More educational programmes should be arranged for pregnant women at hospitals or through the media to enhance their understanding and knowledge of the vaccine. This will contribute to the global effort to combat the effects of future pandemics by increasing vaccination acceptance rates among pregnant women.